2009
DOI: 10.1111/j.1365-2095.2008.00613.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of methionine on intestinal enzymes activities, microflora and humoral immune of juvenile Jian carp (cyprinus carpiovar. Jian)

Abstract: An 8-week feeding experiment was conducted to determine the effect of dietary methionine supplementation on intestinal microflora and humoral immune of juvenile Jian carp (initial weight of 9.9 ± 0.0 g) reared in indoor flow-through and aerated aquaria. Eight amino acid test diets (350 g kg )1 crude protein, CP), using fish meal, soybean-condensed protein and gelatin as intact protein sources supplemented with crystalline amino acids, were formulated to contain graded levels of methionine (0.6-22.0%) at a cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
68
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(86 citation statements)
references
References 24 publications
15
68
2
1
Order By: Relevance
“…Furthermore, studies had demonstrated that MHA was converted into L-methionine for effective utilization in chicken liver, rat liver and hog kidney [11]. Our laboratory previous study found that dietary DL-methionine could improve serum lysozyme activity, total iron-binding capacity, haemagglutination titre, complement 3, 4 and immunoglobulin M (IgM) contents in Jian carp [4]. These appear that MHA can also affect fish immune response, which needs investigation.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Furthermore, studies had demonstrated that MHA was converted into L-methionine for effective utilization in chicken liver, rat liver and hog kidney [11]. Our laboratory previous study found that dietary DL-methionine could improve serum lysozyme activity, total iron-binding capacity, haemagglutination titre, complement 3, 4 and immunoglobulin M (IgM) contents in Jian carp [4]. These appear that MHA can also affect fish immune response, which needs investigation.…”
Section: Introductionmentioning
confidence: 90%
“…Studies indicated that methionine deficiency led to depressed survival rate, as well as reduced growth performance in Jian carp (Cyprinus carpio var. Jian) [4], rainbow trout (Oncorhynchus mykiss) [5] and juvenile red drum (Sciaenops ocellatus) [6]. Supplement methionine hydroxy analogue (MHA), a common used synthetic methionine source, to methionine-deficient diets increased survival rate and also improved growth performance of rainbow trout [5] and juvenile red drum [6].…”
Section: Introductionmentioning
confidence: 99%
“…The present study showed that liver weight was significantly increased with dietary methionine supplementation, and similar result was observed in juvenile Jian carp, Cyprinus carpio var. Jian (Tang et al 2009). In juvenile rockfish (Yan et al 2007) and Atlantic salmon (Espe et al 2008), HSI was influenced by dietary methionine level.…”
Section: Aquaculture Nutritionmentioning
confidence: 97%
“…in ileum of rabbits [39]. Moreover, our laboratory studies showed some amino acids such as methionine [40], histidine [8] and valine [9] affect microbial population in the intestine of Jian carp. So it is necessary to investigate the relationship between dietary Ile and intestinal microbial population in fish.…”
Section: Introductionmentioning
confidence: 99%